Paciente masculino de 61 años con hipertensión arterial y obesidad grado 1 - Malagón Ramos, Shirley Lilibeth (2020)
The following clinical case is based on a 61-year-old male patient, is a taxi driver, with a history of Obesity, within the family pathological background, father suffered from pressure; Patient goes to a doctor's office for presenting a clinical picture of dizziness, blurred vision, headache, imbalance, nosebleeds and low back pain, with fear of suffering from hypertension, because his father died of this disease. The treating doctor for the common signs that the patient presents, sends him to take his blood pressure every day for a week; The Comprehensive Nutritional Assessment was carried out and is determined by BMI Grade I obesity with moderate cardiovascular risk; The biochemical tests were performed and their results reflected, hypertriglyceridemia, hypercholesterolemia, after obtaining all the data of the patient is diagnosed with Arterial Hypertension. An individualized nutritional plan is made that covers the patient's caloric requirement, the type of diet that should be taken will be the DASH diet, will be divided into 4 meals a day, this diet is based on being rich potassium, rich in fruits and vegetables, Low in sodium, high in fiber, monounsaturated and polyunsaturated fats which will normalize the patient's blood pressure. Through the follow-up and monitoring of the patient, considerable weight loss was obtained and their biochemical tests varied favorably and their blood pressure decreased, thus reducing other complications in the patient.